Effects of Divided Attention at Retrieval on Conceptual Implicit Memory - Prull, Matthew W.; Lawless, Courtney; Marshall, Helen M.; Sherman, Annabella T. K. (Frontiers in Psychology, 2016)
This study investigated whether conceptual implicit memory is sensitive to process-specific interference at the time of retrieval. Participants performed the implicit memory test of category exemplar generation (Experiments 1 and 3), or the matched explicit memory test of category-cued recall (Experiment 2), both of which are conceptually-driven memory tasks, under one of two divided attention (DA) conditions in which participants simultaneously performed a distracting task. The distracting task was either syllable judgments (dissimilar processes), or semantic judgments (similar processes) on unrelated words. Compared to full attention (FA) in which no distracting task was performed, DA had no effect on category exemplar generation priming overall, but reduced category-cued recall similarly regardless of distractor task. Analyses of distractor task performance also revealed differences between implicit and explicit memory retrieval. The evidence suggests that, whereas explicit memory retrieval requires attentional resources and is disrupted by semantic and phonological distracting tasks, conceptual implicit memory is automatic and unaffected even when distractor and memory tasks involve similar processes.